LEGAL PROTECTION MEASURES AGAINST THE DISTRIBUTION OF EXPIRED FOOD IN SEMARANG CITY - Analia, Rindu Bening; Suliantoro, Adi; Saputra, Arikha (Jurnal Ilmiah Advokasi, 2025)
Expired food refers to products that have passed their consumption date or expiry date. In Semarang, four modern retailers have been found selling expired food products, including gift packages and canned goods. This study aims to identify the legal protections and responsibilities of businesses regarding the circulation of expired food in Semarang, as well as the roles of the local government and the community in addressing this issue. The research employs a normative juridical approach, analyzing relevant regulations descriptively and qualitatively. Findings indicate that legal protection is outlined in Article 1508 and 1509 of the KUHPer; Article 3, 4(a), 8(1)(g), and 8(2) of Law No. 8 of 1999 on Consumer Protection; Article 3 and 9 of Minister of Health Regulation No. 180/MEN.KES/IV/1985 on Expired Food; Article 86(2), 90(1), and 99 of Law No. 18 of 2012 on Food; and Article 146(1), 147(1), and 148 of Law No. 17 of 2023 on Health. Business operators are responsible for providing compensation, while government bodies such as BPOM and LPKSM, including LP2K, are tasked with overseeing the matter.Keywords: Legal Protection; Food; Expiry.